Paleoenvironmental Reconstruction of Glaciovolcanism in the Cascades of the Pacific Northwest: Implications of Potential Habitable Environments on Mars - Glenister, Chase; Cameron, Barry (Proceedings of the Wisconsin Space Conference, 2022)
The interaction between volcanic processes and glacial ice is termed glaciovolcanism and is a process that is prevalent on Earth and potentially once prevalent on Mars. Such processes are dynamic, forming potentially habitable environments under glacial ice. This work will attempt to describe the glaciovolcanic deposits at the Crazy Hills and Lone Butte in central Washington and evaluate the potential habitability of these glaciovolcanoes. The identification of pillow lavas and thick hyaloclastite beds point to the hosting glacier being at least 300m thick, although precise estimation is not possible at this time. X-ray fluorescence results show that the two provinces shared a magmatic source deep in the mantle and evolved separately to form the Crazy Hills basalt and Lone Butte basaltic andesite. The identification of putative biogenic alteration textures in the pillow rims of the Crazy Hills basalt indicates a stronger potential for habitable conditions in a glaciovolcanic environment.